О целесообразности типологической презентации языка в курсе РКИ - Борисовна Лихачева, Алла (Slavistica Vilnensis, 2009)
The article discusses one of the options for the conscious learning of Russian by foreigners. This is achieved by applying methods of contrastive typological analysis to the target language and the most common linking language, which is English at present. The compiled typological table of the Russian language visually demonstrates structural differences from English, which will be at the centre of attention during the course of Russian for foreigners. A detailed analysis of the Russian phonological system (as compared to the English one) is provided. A similar table could be compiled for any homogeneous ethnic target group. It could be based on cross-linguistic differences of any given language because the rational teaching of a foreign language should generally rest on the data pertaining to the domain of contrastive typological research.